Influence of Laser Pulse Parameters on the Properties of e–e+ Plasmas Created from Vacuum. Issue 2 (31st January 2013) - Blaschke, D. B.; Kämpfer, B.; Panferov, A. D.; Prozorkevich, A. V.; Smolyansky, S. A.
Abstract We use the low density approximation within the kinetic theory approach to vacuum creation of an e–e+ pair plasma (EPPP) in a strong laser field in order to investigate the dependence of the observed EPPP on the form and parameters of a single laser pulse. The EPPP distribution function is calculated for an arbitrary time dependence of the electric field in the multiphoton domain (adiabaticity parameter γ > 1). The dependence on the field strength, the form and spectrum of the field pulse is investigated on the basis both analytical and numerical methods. The obtained results can be useful for examining some observable secondary processes associated with the dynamical Schwinger effect. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)